Legal Analysis Of The Lease Agreement - Farid Azmi (International Asia Of Law and Money Laundering, 2022)
Leasing is a form of business that can be used as an alternative to overcome capital difficulties in the framework of financing a company. The presence of leasing for companies has an important role in helping entrepreneurs in Indonesia, both for small, medium and large businesses. Through leasing activities, these entrepreneurs will quickly be able to overcome the financing method to obtain the equipment and capital goods they need. With less burdensome requirements and a flexible funding system, entrepreneurs love it. This condition, among others, causes the leasing business in Indonesia to develop rapidly. Leasing is one of the business fields included in the scope of financing institutions. Based on the decree of the Minister of Finance of the Republic of Indonesia number 1169 / KMK.01/1991 regarding leasing business activities, what is meant by leasing or leasing is financing activities in the form of capital goods provision, either on lease and option rights (finance lease) or operating lease for use by leasing for a certain period of time based on periodic payments.